Sequent calculus for logic of correlated knowledge - Giedra, Haroldas; Sakalauskaitė, Jūratė (Lietuvos matematikos rinkinys, 2011)
Sound and complete sequent calculi for general epistemic logic and logic of correlated knowledge are presented in this paper.